Genetic engineering of sex chromosomes for batch cultivation of non-transgenic, sex-sorted males - Das, Siba R.; Maselko, Maciej; Upadhyay, Ambuj; Smanski, Michael J. (PLoS genetics, 2020)
The field performance of Sterile Insect Technique (SIT) is improved by sex-sorting and releasing only sterile males. This can be accomplished by resource-intensive separation of males from females by morphology. Alternatively, sex-ratio biasing genetic constructs can be used to selectively remove one sex without the need for manual or automated sorting, but the resulting genetically engineered (GE) control agents would be subject to additional governmental regulation. Here we describe and demonstrate a genetic method for the batch production of non-GE males. This method could be applied to generate the heterogametic sex (XY, or WZ) in any organism with chromosomal sex determination. We observed up to 100% sex-selection with batch cultures of more than 10 3 individuals. Using a stringent transgene detection assay, we demonstrate the potential of mass production of transgene free males.